A prospective randomized controlled trial for assessment of perineal hydrodissection technique for nervesparing robot assisted radical prostatectomy - Hatiboglu, Gencay; Simpfendörfer, Tobias; Uhlmann, Lorenz; Bergero, Miguel A.; Macher-Göppinger, Stephan; Pahernik, Sascha; Hadaschik, Boris; Hohenfellner, Markus; Teber, Dogu (The international journal of medical robotics and computer assisted surgery, 2017)
Background This study prospectively evaluated the safety and efficacy of perineal hydrodissection in robot assisted nervesparing prostatectomy. Methods Patients were randomized for perineal, ultrasound guided hydrodissection (HD) before radical prostatectomy and compared with standard treatment (ST). Follow-up was done every 3 months, including erectile function (IIEF5-score), reported grade of erection, ability for sexual intercourse, continence, PSA. Results 21 patients were enrolled to this prospective study, 10 for ST and 11 for HD. No significant differences in demographic and preoperative oncological data between both groups were identified. Blood loss and time for surgery did not differ significantly. HD resulted in 66% (4/6) rate of positive surgical margins (PSM) in pT3 tumors vs 50% in ST (1/2; P = 0.67). Follow-up revealed higher IIEF scores, better ability for sexual intercourse and early continence in HD. Conclusions Erectile function after radical prostatectomy was improved by perineal hydrodissection in this proof of principal study. However, careful patient selection and further studies are needed as perineal hydrodissection could result in increased positive surgical margins in pT3a tumors.